The Interaction of Genetic Mutations in PARK2 and FA2H Causes a Novel Phenotype in a Case of Childhood-Onset Movement Disorder - Benger, Matthew; Mankad, Kshitij; Proukakis, Christos; Mazarakis, Nicholas D.; Kinali, Maria (Frontiers in Neurology, 2019)
Mutations in the PARK2 gene have been implicated in the pathogenesis of early-onset Parkinson’s disease. We present a case of movement disorder in a 4 year-old child from consanguineous parents and with a family history of Dopamine responsive dystonia, who was diagnosed with early-onset Parkinson's disease based on initial identification of a pathogenic PARK2 mutation. However, the evolution of the child's clinical picture was unusually rapid, with a preponderance of pyramidal rather than extra-pyramidal symptoms, leading to re-investigation of the case with further imaging and genetic sequencing. Interestingly, a second homozygous mutation in the FA2H gene, implicated in Hereditary spastic paraplegia, was revealed, appearing to have contributed to the novel phenotype observed, and highlighting a potential interaction between the two mutated genes.